Selection and Training of Leaders in the Turkish Armed Forces - Begeç, Suat (International Review of Management and Marketing, 2013)
Leadership is the most frequently studied concept at the beginning of every period of history. Leader is a commander and the leadership is a command the unit in military sense. The majority of studies about leadership are conducted in the armed forces. Many countries have designed their armies in accordance with these studies. The Turkish Armed Forces (TAF) believes the importance of these studies and designs education systems and training in the selection and training of the leaders. The biggest advance in the TAF was being held during the period of education and training improvement. This study investigates to bring that issue into focus and offers a whole social science agenda for leadership in the TAF related research. In this article exploratory research was applied and military history specimens were used. The results of the study demonstrate the geographically powerful armed forces are always needed. A powerful army can indicate the presence of strong leadership. The criteria determined by the selection and training of staff will be one of the most essential tasks that will lead the TAF into the future. These results, however, need further work to validate reliability. Key words: army; leader; military schools; training JEL Classification: M00; M53